Effect of concentration on the structure of isothermally-annealed CuZr metallic glasses. Issue 18 (12th December 2018) - Yue, X. X.; Liu, C. T.; Pan, S. Y.; Inoue, A.; Liaw, P. K.; Fan, C.
ABSTRACT: To clarify the influence of isothermal annealing on Cux Zr100-x ( x  = 36, 44, 50, 56, and 64) metallic glasses, the annealing process was conducted using molecular dynamics (MD) simulation. The local structure is analysed by means of the radial distribution functions, Voronoi tessellation and the nearest-neighbour correlation index, Cij . The results show that Cu-centered < 0 0 12 0 > and Zr-centered < 0 0 12 4 > dramatically increases after an isothermal annealing treatment and presents a strong tendency of being the nearest neighbour with each other, as the Cu concentration is over 50%. These two kinds of clusters are formed the Cu2 Zr Laves phase which can be directly observed in the Cu-rich glasses.